PENGEMBANGAN PEMBANGKIT LISTRIK TENAGA PICO-HYDRO DENGAN MEMANFAATKAN ALTERNATOR UNTUK MEMBANTU PENERANGAN JALAN SEPUTARAN KEBUN SALAK - Alipan, Nurva (Jurnal Edukasi Elektro, 2018)
Abstract The final project is aimed at realizing a Pico-hydro Power Plant that can be used for street lighting around the salak garden, as well as find out the performance of the pico-hydro power plant which can be used for electrical energy needs such as street lighting. Design and manufacture of pico-hydro power plant requires several supporting components such as: (a). Pelton type turbine; (b). 3 phase AC generator; (c). Accumulator 12volt 3.5Ah; (d). 3 phase full phase rectifier circuit; (e). Charger control regulator circuit; (f). Inverter circuit; And (g). Energy saving lamps. The process of the beginning includes: (a). Analyzing the needs of both equipment and materials needs, (b). Do the design process, (c). Design of Pico Hydro Power Plant (PLTPH), (d). Testing tool. Based on the performance test results, Pico-Hydro Power Station can work well. This can be seen from the indicators of high water flow discharge can rotate the turbine quickly during the rainy season the flow of water will be higher turbine will also spin faster. Water discharge is very influential on the rotation of the generator, if the water discharge is high then the charging will be faster. Conversely when the water discharge decreases the charging will be long. The average water discharge of 0.061 - 0.065 can rotate the 371 rpm generator producing an average voltage of 17.5 volts. At a voltage generated from an inverter of 220 Volts can supply a number of 5-sized lamps 15 Watt. The result of the generator test produces a voltage of 12 V AC with a current of 2 Ampere converted to an inverter DC voltage to AC to 220 V with 100 Watt power. Keywords : pico-hydro, 3 phase AC generator, water discharge Abstrak Penelitian ini bertujuan untuk merealisasikan sebuah Pembangkit Listrik Tenaga Pico-hydro yang dapat digunakan untuk penerangan jalan seputaran kebun salak, serta mengetahui unjuk kerja dari pembangkit listrik tenaga pico-hydro yang nantinya dapat digunakan untuk kebutuhan energi listrik seperti penerangan jalan. Perancangan dan pembuatan pembangkit listrik tenaga pico-hydro membutuhkan beberapa komponen pendukung diantaranya: a). turbin berjenis pelton; b). generator AC 3 fasa; c). accumulator 12volt 3,5Ah; d). rangkaian penyearah gelombang penuh 3 fasa; e). rangkaian charger control regulator; f). rangkaian inverter; dan g). lampu hemat energi. Proses pembuatan alat, meliputi: a). menganalisis kebutuhan baik kebutuhan alat dan bahan, b). melakukan proses perancangan, c). pembuatan desain Pembangkit Listrik Tenaga Pico Hydro (PLTPH), d). pengujian alat. Berdasarkan hasil uji kinerja, Pembangkit Listrik Tenaga Pico-Hydro dapat bekerja dengan baik. Hal ini dapat dilihat dari indikator debit aliran air yang tinggi dapat memutar turbin dengan cepat. Saat musim hujan aliran air akan semakin tinggi sehingga turbin juga akan berputar lebih cepat. Debit air sangat berpengaruh terhadap putaran generator, jika debit air tinggi maka pengisian akan lebih cepat. Sebaliknya saat debit air menurun pengisian akan lama. Debit air rata-rata 0,061 - 0,065 dapat memutar generator 371 rpm menghasilkan tegangan rata-rata 17,5 volt. Pada tegangan yang dihasilkan dari inverter sebesar 220 Volt dapat mensuplai sejumlah lampu 5 berukuran 15 Watt. Hasil pengujian generator menghasilkan tegangan 12 V AC dengan arus 2 Ampere dikonversi ke inverter tegangan DC ke AC menjadi 220 V dengan daya 100 Watt. Kata kunci: pico-hydro, generator AC 3 fasa, debit air